Parasympathetic Activity, Psychological Stress, and Their Relationship to Scoring Accuracy among Female Futsal Players - طيبة سليم, عبد المجيد (Journal of Sport Science Technology and Physical Activities, 2026)
The study aims to identify the relationship between parasympathetic nervous system hyperactivity, psychological stress, and shooting accuracy among futsal players. For this purpose, the descriptive method was used on a sample consisting of (75) players who were selected intentionally. To collect data, a skill performance test was employed along with a psychological stress questionnaire. After collecting and statistically analyzing the results, it was found that parasympathetic hyperactivity and psychological pressures from the audience and the media have an effect on the players’ performance levels. Accordingly, the study recommended activating the role of psychological preparation to reduce psychological stress and working to restore autonomic nervous system balance through organizing courses conducted by specialists in sports psychology in cooperation with the Iraqi Football Association.